Do cleaner fish learn to feed against their preference in a reverse reward contingency task? - Danisman, Evin; Bshary, Redouan; Bergmueller, Ralph (My University, 2010)
The ability to control impulsive behaviour has been studied in animals with a standard test in which subjects need to choose the smaller of two food items in order to receive the larger one (reverse reward contingency). As a variety of mammals that have been tested so far (mostly primates) have great difficulties to solve the task, it has been proposed that it is generally cognitively demanding. However, according to an ecological approach to cognition, a species’ ability to solve the task should not depend on its general cognitive abilities but on whether its ecology causes selective pressure on the ability to restrain foraging behaviour. We tested this hypothesis using the cleaner wrasse (Labroides dimidiatus), a fish species that feeds against its preference in nature when engaging in cleaning interactions with so called ‘client fish’. None of the eight tested individuals learned to choose a non-preferred item after 200 trials. In a subsequent test, one subject learned to respond correctly in a large or none contingency task (only the choice of the small food was rewarded). After a short re-experience treatment, this individual learned to solve the reverse reward task after 30 trials. In conclusion, we did not find support for the general idea that interactions with clients prepared cleaners to quickly solve a reverse reward test. However, the results suggest that the potential to solve a reverse reward contingency may not be restricted to mammals but could be present also in a fish species in which the problem of choosing a non-preferred food over a preferred one is an ever present challenge in nature.
Keywords: Reverse reward contingency; Impulse control; Ecological approach to cognition; Cleaner fish; Animal cooperation; Learning